Tannery effluent induced morpho-biochemical expressions and chromium accumulation in Jatropha curcas L. and Pongamia pinnata L. - Abid, Rafia; Mahmood, Seema; Ghaffar, Shazia; Saman, Zahra; Sibgha, Noreen (Penerbit Universiti Kebangsaan Malaysia, 2019)
The use of effluent from various industries by agriculture sector in developing countries may help to mitigate water scarcity and cost of fertilizers but pose considerable threats to entire ecosystem when heavy metals enter the food chain. The aim of the present study was to compare the growth and development of two biofuel tree species Jatropha curcas L. and Pongamia pinnata L. when exposed to 20 and 40 mL L−1 of effluent discharged from a local tannery along with tap water as a control. The physico-chemical attributes assessed for quality of effluent showed higher values and significantly higher chromium (Cr) concentration than other metals. Application of effluent induced profound formation of malondialdehyde (MDA) in P. pinnata. With regard to growth and pigments of plant species, a significant reduction (p≤0.05) in root length, dry shoot biomass, leaf area, chlorophylls and carotenoids occurred in P. pinnata but shoot length, collar diameter and root dry biomass remained unaffected. Similarly, J. curcas sustained root and shoot growth, dry biomass production, collar diameter and leaf area. Increased pigment contents were found at both effluent levels. The roots of P. pinnata accumulated 6 and 11 times more Cr at 20 and 40 mL L−1, respectively, than control. While in J. curcas Cr accumulation was up to 9 folds in shoots at 40 mL L−1. Thus, the two species exhibited differential potential for Cr accumulation in their above and below ground tissues. The study signified the use of contaminated water for irrigation and potential of the species to act as phytoremediator to alleviate both water scarcity and metal contamination.